Optimasi Parameter Mesin Fused Deposition Modelling (Fdm) Terhadap Kekasaran Permukaan Produk Menggunakan Metode Taguchi - Bayu Wiro Karuniawan, Farizi Rachman, Andik Aris Setiawan (Techno Bahari, 2019)
The research was conducted using a FDM (Fused Deposition Modeling) Rapid Prototyping machine with various combinations of parameters. Selection of parameters for 3 types of parameters, each parameter varied by 3 variations. The material used is PLA (polylactic acid) material. The research method uses the Taguchi method. The resulting response is only surface roughness. Experiments produce the optimum parameters: Print Speed 60 mm/s, Printing Temperature 200 ° C, Layer Height 0.1 mm